LISTENING IN VERBAL COMMUNICATION - Simona RODAT (Annals of the University of Craiova for Journalism, Communication and Management, 2019)
In communication between people, listening plays an important role. Active listening, which implies giving the full attention to the speaker and showing interest to the communication by using a variety of verbal and non-verbal signs, maintains the communication relations and contributes to mitigating conflicts in different social contexts. Moreover, active listening is the most desirable form of response in the interaction between interlocutors, in activities where communication and comprehension are essential, as is the case with social work. Starting with the delineation of the place of listening in the verbal communication and the outlining of the characteristics of the active listening, this paper deals further with the ways in which the importance and the roles of listening and active listening are highlighted in the theoretical and methodological models of intervention developed in social work.